Effect of normal pressure on the critical compressive stress of curved sheet - Rafel, Norman (National Advisory Committee for Aeronautics, 1942)
Results are presented of tests of two specimens tested to study the effect of normal pressure on the critical compressive stress for thin curved sheets. These specimens are designated by their respective rib spacings of 10 inches and 30 inches. The relationship between compressive stress and normal pressure at which buckles disappeared is independent of whether the buckles were made to disappear by increase of normal pressure or decrease of compressive stress.
NACA Wartime Report L-258.
Originally issued as NACA as a Restricted Bulletin (November 1942).
Prepared at the Langley Memorial Aeronautical Laboratory, Langley Field, Virginia.
Keywords: Atmospheric pressure.; Buckling (Mechanics); Strains and stresses.; Loads (Mechanics); Charts, diagrams, etc.; elektronické knihy; electronic books